Business law and the regulatory environment : concepts and cases - Metzger, Michael B.; Mallor, Jane P.; Barnes, James A.; Bowers, Thomas; Phillips, Michael J. (Homewood, Ill. : Irwin, 1986)
The book provides context and essential concepts across the entire range of legal issues with which managers and business executives must grapple
Kept up to date by "annual update."
Includes bibliographical references and indexes.
lje,19/06/17
Loan
Keywords: Commercial law; Business law; Regulatory enviroment